Modulating effects of Phellinus linteus polysaccharides on antioxidant capacity, immune function, intestinal function and microbiota in lipopolysaccharide-challenged broilers - Li, Yang; Wang, Shuai; Zhu, Xuran; Gao, Nana; Kang, Jungang; Wang, Tianxiong; Wang, Xiaodan (Frontiers in Microbiology, 2025)
Phellinus linteus polysaccharides (PLP) have been shown to have beneficial effects on gut function and gut microbiota in animals. The intention of this study was to examine the effects of PLP on growth performance, immune function, intestinal barrier function and intestinal microbial community in broilers under lipopolysaccharide (LPS) challenge. A total of 120 one-day-old Arbor Acres (AA) broilers were randomly allocated into 3 groups: control, LPS, and PLP + LPS. The PLP + LPS group had 200 mg/kg/d PLP added to the ration in the daily trial. LPS and PLP + LPS group were intraperitoneally injected with LPS on days 14, 16, 18, and 20. The results demonstrated that LPS significantly decreased average daily gain (ADG), average daily feed intake (ADFI), and total antioxidant capacity (T-AOC) activity in serum and duodenum. Additionally, LPS reduced the mRNA expression levels of ZO-1 and Occludin in duodenum, increased spleen bursal index, and MDA activity in serum and duodenum (P < 0.05). Histological examination revealed that LPS caused duodenal damage, leading to intestinal mucosal injury and shedding, villus height reduction, and crypt depth increase. PLP inclusion mitigated the adverse impacts of LPS on key parameters (P < 0.05). Furthermore, gut microbiota analysis revealed that PLP supplementation increased the ratio of Firmicutes to Bacteroidetes. At the genus level, the addition of PLP decreased the abundance of Bacteroides and Escherichia-Shigella, while simultaneously increased the presence of Akkermansia, Faecalibacterium, Lactobacillus, and Parabacteroides. In summary, supplementing the dietary inclusion with 200 mg/kg of PLP enhances growth, immune function, and antioxidant capabilities in LPS-challenged broilers. This improvement is likely attributed to the modulation of gut microbiota community composition.